2018
DOI: 10.3233/jad-170751
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Loss Predicts Poorer Spatial Cognition in Patients with Alzheimer’s Disease

Abstract: The vestibular system is an important contributor to balance control, spatial orientation, and falls risk. Recent evidence has shown that Alzheimer's disease (AD) patients have a higher prevalence of vestibular impairment relative to healthy controls. We sought to evaluate whether vestibular loss is specifically associated with poor spatial cognitive skills among patients with mild cognitive impairment (MCI) and AD. We enrolled 50 patients (22 MCI and 28 AD) from an interdisciplinary Memory Clinic and measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 54 publications
5
36
0
3
Order By: Relevance
“…In particular, vestibular dysfunction and impaired vestibular balance control were more frequently reported in patients with MCI or Alzheimer’s dementia. In this study, we found that MCI patients with dizziness performed significantly worse on the COWAT, one of the tests assessing verbal fluency and executive function, than MCI patients without dizziness, which is consistent with previous studies that showed executive function impairment among patients with dizziness [ 10 , 31 ]. Notably, frontal areas, especially the lateral pars orbitalis, were found to be associated with the letter-based phonemic COWAT among AD patients [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In particular, vestibular dysfunction and impaired vestibular balance control were more frequently reported in patients with MCI or Alzheimer’s dementia. In this study, we found that MCI patients with dizziness performed significantly worse on the COWAT, one of the tests assessing verbal fluency and executive function, than MCI patients without dizziness, which is consistent with previous studies that showed executive function impairment among patients with dizziness [ 10 , 31 ]. Notably, frontal areas, especially the lateral pars orbitalis, were found to be associated with the letter-based phonemic COWAT among AD patients [ 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that having dizziness is related to subjective memory complaints or cognitive dysfunction in various domains including visuospatial, memory, and executive function [ 4 , 6 , 13 , 31 , 32 ]. This phenomenon was also observed in patients with AD-related cognitive impairment [ 10 , 33 ]. In particular, vestibular dysfunction and impaired vestibular balance control were more frequently reported in patients with MCI or Alzheimer’s dementia.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Subjects with impaired memory or spatial navigation abilities (such as hippocampal lesions) fail to locate the platform and wander erratically around for a long period of time, even after having found the platform in previous trials. For human testing, virtual versions of the MWM paradigm have been validated and proved for use in identifying memory impairments, such as those found in individuals with Alzheimer's disease (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%